Spatial patterns of mayfly, stonefly and caddisfly assemblages in Swiss running waters in the face of global warming. Issue 7 (26th March 2020) - Timoner, Pablo; Marle, Pierre; Castella, Emmanuel; Lehmann, Anthony
Abstract : Biotic homogenization represents a major concern in ecology but relatively few studies have assessed climate change impacts on assemblage patterns of freshwater species. Our main goals were to predict the current and future (years 2035, 2060 and 2085) patterns of mayfly, stonefly and caddisfly (EPT) diversity across Switzerland from macroscale environmental variables, and to assess the impact of warming temperatures on β‐diversity. The study area was the entire Swiss territory divided into 21 818 subcatchments (median area of 1.41 km 2 ), used as spatial units for predicting patterns of EPT diversity. We assumed that the stream conditions were homogeneous within a subcatchment at this scale. Incidence of EPT larvae was derived from samplings carried out between 2010 and 2017 in 292 water‐course sites as part of two national monitoring programs. We employed generalized dissimilarity modeling to analyze the spatial turnover of EPT assemblages. Climatic, topographic, geological and land‐use variables were used as covariates, and different climate change scenarios were used for future predictions. We compared β‐diversity among the different scenarios through distance‐based tests of homogeneity of multivariate dispersions. Our findings showed the largest amount of EPT turnover occurred along the air temperature and slope gradients, considered as good proxies for water temperature and flow velocity. We predicted a biotic homogenization with increasing temperatures due to the upstream expansion of some species from the sub‐montane level, which only stabilizes in the most conservative climate scenario. This study is the first countrywide prediction of EPT composition patterns in the context of global warming and provides insights into the vulnerability of assemblages occurring at high elevations.